EXPLORING MARKETING STRATEGY TO INCREASE SALES FOR BAJA PERKASA ROOF CASE - Permana, Dhidhi Indra (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This study aims to analyze the internal and external conditions of Baja Perkasa Roof, the factors influencing client decisions to purchase sand metal roofing, and the strategies that can be implemented to increase sales figures. The results of the study show that Baja Perkasa Roof's internal and external conditions have several strengths, such as a large daily production capacity (6,000 meters), certified products from the Balai Besar Standarisasi dan Pelayanan Jasa Industri Bahan dan Barang Teknik (Center for Standardization and Industrial Services for Materials and Technical Goods), product warranties, chemical-free products, and a reliable delivery fleet. However, there are some weaknesses, including higher product prices compared to competitors, the absence of its own tile moulding machine, lack of drying machines, a non-integrated administrative system, and no product patents. The factors influencing client decisions to purchase sand metal roofing products include good product quality, product price, ease and flexibility of payments, and satisfactory delivery services. The strategies recommended based on the TOWS analysis to increase Baja Perkasa Roof's sales figures include producing lower-priced products to compete with competitors, aggressively promoting certified products, offering a loyalty point program to customers, and purchasing its own tile moulding machine.